(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
This article summarises the findings of ethnobotanical research conducted among the Digo people of Kwale District, Kenya, together with applications of this research for the benefit of the local community and implications of this for language vitality. The article consists of four sections. Section 1 provides background information on the Digo people and language, the ecology of the region, and the research methodology employed. Section 2 discusses Digo botanical folk taxonomy, that is, the way in which Digo speakers classify plants, and the ways in which this differs from botanical folk taxonomies reported for neighbouring Swahili speakers. Section 3 provides details of medicinal and other uses of a sample of 30 plants. Finally, in Section 4 the relevance of such studies is related to the current debate on the maintenance and interrelation of linguistic, cultural and biological diversity.